Analisis Sektor Unggulan dan Transformasi Struktural di Provinsi Kalimantan Tengah 2010 – 2016 - Maria Christina; Yuli Pratiwi (Balitbangda Provinsi Lampung, 2017)
: Development and economic growth are two interrelated things. Both of these things will not run optimally if the development process does not pay attention to the potential of the region. By identifying the leading sectors, the potential of the region can be known so that the development planning runs effectively and efficiently. The economic growth rate of Central Kalimantan Province is the highest in Kalimantan. Central Kalimantan Province can obtain a larger GRDP and increase economic growth if able to take advantage of its potential. The purpose of this study is to identify the key sectors that have the potential to develop and analyze these sectors to determine the right development priorities, and to increase local government efforts in supporting the development of superior economic potential. This research is a descriptive quantitative research using secondary data. The results of the study indicate that potential economic sectors based on Location Quotient analysis, Klassen Tipology, Shift Share analysis, and Overlay analysis are the agricultural, forestry and fishery sectors, the manufacturing sector, and the large and retail trade sectors. Central Kalimantan's economy undergoes a structural transformation characterized by a decline in the role of the agricultural sector, and the increasing role of the industrial and service sectors. Central Kalimantan Provincial Government's support can be seen from Regional Long Term Development Plan (RLTDP) and Regional Medium Term Development Plan (RMTDP), and from Regional Budget Revenue and Expenditure (RBRE) allocations that have prioritized and focused economic development on the leading sectors.